2013
DOI: 10.5552/drind.2013.1317
|View full text |Cite
|
Sign up to set email alerts
|

Application of Risk Analysis in Business Investment Decision-Making

Abstract: • Investment decision-makings should be regarded in each business entity as the crucial factor for its long-term prosperity. An acquired decision affects the performance of the company as well as its competitiveness in long time. If a competent investor has an interest to make a qualified investment decision, it means that he must

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…An acquired decision affects the company's performance and its competitiveness for a long time. If a competent investor is interested in making a qualified investment decision, he must primarily determine the time and risk factors [41]. The beta coefficient is an integral component of the CAPM model that quantifies the relationship between systematic risk and the expected return.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An acquired decision affects the company's performance and its competitiveness for a long time. If a competent investor is interested in making a qualified investment decision, he must primarily determine the time and risk factors [41]. The beta coefficient is an integral component of the CAPM model that quantifies the relationship between systematic risk and the expected return.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This method was implemented in furniture manufacturing of wood with the objective to identify critical factor that affect the expected profit and cash flow in the execution of investment projects (Merková et al, 2013). The results of the sensitivity analysis of the project by changing the values of the project by ± 10 %, show that the main risk factors that cause the decrease in profit were the sale price, the volume of production, the cost of materials and the labor costs.…”
Section: Introductionmentioning
confidence: 99%
“…The investment in learning and development of talents (Garavan et al 2012) has been justifi ed as a source of competitive advantage. Garavan (2012) concluded that external talent acquisition strategy has proven to be unsuccessful in the long run with many organisations (Merková et al, 2013). Lepak and Snell (1999) and Stacho and Stasiak-Betlejewska (2014) determined relative advantage of organisations developing their workforce internally.…”
Section: Uvodmentioning
confidence: 99%